Implementation of Repression Policy in Kirghiz SSR in 1937—1938 - B. D. Abdrakhmanov; Z. A. Altymyshova (Научный диалог)
The issue of the implementation of repressions against the “Trotskyists”, “Zinovievites”, “Rightists” and other “enemies of the people” living in the Kirghiz SSR in 1937—1938 is examined in the article. Both objective and subjective prerequisites for the punitive activities of the security agencies in the first years of Soviet power are considered. The relevance of the study is due to the interest of scientists and the public in the period of Stalinist repressions, the assessment of these events. The study was carried out on the basis of materials from the archives of the State Committee for National Security. The novelty of the research is due to the fact that these documents are introduced into scientific circulation for the first time. In addition, statistics are provided on some categories of repressed in the republic, which are also published for the first time. A rethinking and political assessment of the events of this difficult period is proposed. The repressive activities against the so-called “enemies of the people” in the political aspect are analyzed, since the special services were an instrument of the ruling party and obeyed. The role and place of the security agencies, the mechanism for implementing repressions and illegal methods of conducting investigations based on archival documents of the State Committee for National Security of the Kyrgyz Republic are shown.